Identification of protein extracts from cysticercus tenuicollis using SDS–PAGE method collected from sheep in slaughterhouse, Kerbala Provenance, Iraq - Obead, Jihad Talib; Mohammed, Bariq Abd Alameer; Mahdi, Hayder Talib; Sulbi, Ihsan Mohammed (Eximia, 2025)
Cysticercosis is a disease cause by the cysticercus tenuicollis, An infection caused by metacestodes that impacts a broad range of ruminant animals. When dogs and wild dogs contract the intestinal tapeworm Taenia hydatigena's larval stages, it happens. The adult cysticercus larvae found in the intermediate host's omentum, mesentery, and peritoneum are usually the mature cysticerci's typical sites; the pleura and pericardium are less frequently found. The migratory larvae, which are mostly found in the parenchyma of the liver, can cause traumatic hepatitis overall the young animals. Most infections are found in the slaughterhouse and are chronic and asymptomatic. Acute infection in sheep is rare, and reports of lamb fatalities are rare as well. The Taenia hydatigena larva Cysticercus tenuicollis is frequently seen in Iraqi sheep that have been slaughtered. 25 specimen cysts of Cysticercus tenuicollis were taken from the slaughtered sheep (two cysts per animal) in slaughterhouses in the province of Kerbala during October and November of 2024 for this study. In this investigation, samples of liver from sheep have been slaughtered at the Karbala Abattoir in Iraq were used to acquire fluid from cysts of larval stage (N = 25). The SDS-PAGE method (Sodium Dodecy Sulfate-Polyacrelamide Gel Electrophoresis) was used to test different proteins in the fluids extracted from cysts in order to discover reactive proteins. The results of fluid antigens' SDS PAGE analysis findings showed 73, 51, 45, and 8 kDa. In conclusion, Identifying antigens in helminthes will enhance diagnostic techniques and control them, while investigating the host-parasite connection is crucial for disease control.